Capo Mannu Project 2012 - Prima campagna di scavo del sito di Su Pallosu (San Vero Milis, OR) - Giandaniele Castangia (Traces in Time, 2013)
In this report the author presents the results of the 2012 excavation campaign of the coastal site of Su Pallosu, located in the northern side of the Capo Mannu peninsula in Central Western Sardinia. The site was partially investigated in 2006 and 2007, revealing the presence of a Bronze Age ceramic deposit, featured by a very high density of fragments and a high number of well preserved pluri-handled necked little jars with their lids, covered by a later burial and a couple of thick sandy layers containing almost no archaeological material. The deposit has been interpreted as an indicator of some cultual activity, for the pluri-handled necked little jar form is usually found in sites with some sort of cultual characterization. During the 2012 campaign this stratigraphic sequence was confirmed and the deposit was completely excavated over an area of 44 square meters.